Estrategias cognitivas de aprendizaje en el desarrollo de la retención del léxico en la memoria a largo plazo en la adquisición de un idioma - Zavala, Gilberto Cesar (2018)
The present research is focused on the importance of applying cognitive learning strategies in the classroom as a fundamental educational tool to improve retention of the students’ lexicon, and this way, teachers can power the language vocabulary and facilitate students ́ English language learning. It is important to determine that cognitive learning strategies are a kind of a learning strategy that students use to learn the new language successfully. These techniques include the repetition, organization of the new language, lexical inference, and comprehension of lexical meaning in any context, memorization and retention. All these techniques involve the deliberation, manipulation of the language skills and its lexical information to improve the language learning. The Language Center of the central University of Ecuador was the place where this research was carried on, considering the students of the level A1, or beginners, in the semester during March and August 2016. Within the research process, a survey technique was applied trough a questionnaire tested to 180 students from the Central university of Ecuador belonging to level A1. After analyzing the results of the research, it is necessary to determine the mighty importance to apply cognitive learning strategies, in the development of lexical retention, so that students have a good and real learning of the English language, and, this way there are not difficulties for students to develop their communicative skills in the new language.